Physicochemical compatibility of commonly used analgesics and sedatives in the intensive care medicine. Issue 3 (4th April 2014) - Knudsen, Lena; Eisend, Swantje; Haake, Nils; Kunze, Thomas
Abstract : Objectives: To minimise the risk of incompatibilities in parenteral drugs in a cardiovascular intensive care unit by analysing the physical and chemical compatibility of seven commonly used analgesics and sedatives and to determine whether these drugs can be administered by the same intravenous line. Methods: Clonidine hydrochloride, 4-hydroxybutyric acid, ( S )-ketamine hydrochloride, lormetazepam, midazolam hydrochloride, piritramide and sufentanil citrate were diluted with sodium chloride 0.9% to standardised concentrations, mixed in different ways and combinations and stored for 7 days. During the storage, samples were taken and compatibility was verified by visual and photometrical inspection in terms of precipitation, haze, colour change, production of gas and pH determination. Additionally, the chemical compatibility of two multiple drug mixtures and 10 drug pairs was determined by high-performance liquid chromatography examination. Results: 4-Hydroxybutyric acid was physically incompatible with ( S )-ketamine hydrochloride, midazolam hydrochloride and piritramide. All of the other drug combinations were found to be colourless with no signs of precipitation, haze or production of gas and no deviation of pH by more than 1.0 unit in a time period of 24 h. Chemical compatibility could be established for the two multiple drug combinations and for 9 of 10 drug pairs. The combination of clonidine hydrochloride and sufentanil citrate showed instabilities within the first hours after mixing. Conclusions: 4-Hydroxybutyric acid carries a major risk for incompatibilities when mixed with other drugs and therefore has to be administered separately. Mixtures of clonidine hydrochloride and sufentanil citrate should only be used with great caution, and a dose adjustment should be considered.